Research and application of Rayleigh wave extraction method based on microtremors signal analysis - Du, Qingling; Pan, Yanhui; Xin, Youyang (Frontiers in Physics, 2023)
The microtremor Rayleigh wave exploration is an important part of the seismic wave exploration method, but because the microtremor signal is a weak vibration generated by various factors in nature, the complexity of its composition makes it difficult to extract the Rayleigh wave with high signal-to-noise ratio, which seriously limits the application of this method in engineering. Therefore, this paper studies the method and application of single-channel three-component microtremor signal co-directional Rayleigh surface wave extraction. Firstly, the filtering method of linear polarization wave is studied according to the polarization characteristics and phase difference characteristics of Rayleigh surface wave. The advantages and disadvantages of polarizability wave and phase difference filtering are analyzed based on simulated data and real microtremor signals. Secondly, the application of time-frequency analysis method in the analysis of microtremor signals and the identification of Rayleigh wave propagation direction are studied. Finally, combining the advantages of different filtering methods, a set of procedures for extracting high SNR co-directional Rayleigh surface waves from the microtremor signal is developed, and the method is applied to the elliptical polarizability imaging method. The experimental results show that the data processing process can effectively filter the linear polarization wave and accurately determine the propagation direction of the Rayleigh wave, greatly improving the accuracy of the elliptical polarizability exploration results. It provides a reference for the extraction of high signal-to-noise ratio data of the microtremor Rayleigh wave seismic exploration method.